2021
DOI: 10.1016/j.isci.2021.103461
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the growth of Haematococcus pluvialis based on a novel microbubble-driven photobioreactor

Abstract: Haematococcus pluvialis, the richest bioresource for natural astaxanthin, encounters a challenge of achieving high growth rate when it comes to mass biomass production. Based on the substrate consumption model and Redfield ratio, rapid algae growth benefits from a proper carbon supply. However, the conventional cultivation schemes with limited carbon dioxide (CO 2 ) supply and inefficient carbon mass transfer could have constrained the carbon capture and growing ability of H. pluvialis. We hypothesize that opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
0
6
1
2
Order By: Relevance
“…As demonstrated in Figure 2b, T3 produced a higher value of µmax = 0.71/d on day 6 for H. pluvialis than did cell growth from other treatments. A study found that cultivated H. pluvialis produced a µmax of 0.68/d, which was less than the µmax found in this investigation (Table 3) [30]. Additionally, treatments containing 90% nejayote did not function optimally as a growing medium for S. acutus or H. pluvialis, indicating that these concentrations are not ideal for promoting the growth of microalgae.…”
Section: Biomass Growth Of S Acutus and H Pluvialis In Nejayote And F...contrasting
confidence: 79%
“…As demonstrated in Figure 2b, T3 produced a higher value of µmax = 0.71/d on day 6 for H. pluvialis than did cell growth from other treatments. A study found that cultivated H. pluvialis produced a µmax of 0.68/d, which was less than the µmax found in this investigation (Table 3) [30]. Additionally, treatments containing 90% nejayote did not function optimally as a growing medium for S. acutus or H. pluvialis, indicating that these concentrations are not ideal for promoting the growth of microalgae.…”
Section: Biomass Growth Of S Acutus and H Pluvialis In Nejayote And F...contrasting
confidence: 79%
“…An artificial algal bloom induction experiment was performed from 28 October 2020 (day 0, sample G0) to 26 November 2020 (day 30, samples G1 to G29). The microcosm photobioreactor (PBR) (100 l) was designed according to previous methods ( Wu et al, 2021 ). A total of six PBRs were used, and each acted as an independent biological replicate.…”
Section: Methodsmentioning
confidence: 99%
“…Esta microalga de forma ovoide de alrededor de 30 um se reproduce de forma asexual y crece óptimamente en temperaturas de 25-28 °C. (Wu et al, 2021). Su ciclo de vida consta de dos fases primordiales: la primera es la fase vegetal, en donde es ovoide, biflagelada y cuenta con un único cloroplasto (Oslan et al, 2021); durante esta fase, la microalga se divide de forma asexual.…”
Section: Haematococcus Pluvialisunclassified
“…Células no móviles llamadas palmellas o fase de enquistamiento, en cuya fase la pared celular se vuelve más rígida e inicia la acumulación de astaxantina; 4. Células quísticas de color rojo también conocidas como células maduras o aplanosporas, en cuya maduración los flagelos desaparecen y la pared celular aumenta su grosor (Wu et al, 2021). En la etapa de quiste es en donde se da la mayor producción de astaxantina que es estimulada por los factores de estrés.…”
Section: Haematococcus Pluvialisunclassified